Fusion between contemporary medicine (paracetamol) and prophetic medicine (honey) as pharmaceutical suspension - Md Adib, Noor Adibah; Haris @ Harith, Muhammad Salahuddin; Mohamed, Farahidah (2013)
Commercial paracetamol (PCM) suspension is formulated with high amount of sugar and more than 7 excipients to mask the bitter taste of PCM and to achieve stable pharmaceutical suspension for an acceptable shelf-life. This over-the counter pharmaceutical is rampantly used to alleviate minor ailments and fever especially in infants and children but concern over its high sugar sweeteners content during repeated and prolonged treatment is worrying (e.g. dental caries). As such, this study aims to explore alternative PCM formulation by fusioning the PCM into honey alone without other excipients. Two types of honey have been tested, namely ‘Khaula’ and ‘Tualang’ which differ in viscosity and colour. Different processing variables had been tested as well including type of mixers, temperature and flow rate. The formulation were characterised for their particle size, stability and compatibility and the results were compared with commercial PCM suspension. PCM suspension prepared using highly viscous honey (Khaula) was found to be stable compared to the commercial PCM in contrast to PCM-Tualang suspension. Compatibility study based on Fourier-Transform Infra-Red (FTIR) showed similar spectra for all PCM-honey as compared to commercial PCM. Particle size of PCM-Khaula was larger than PCM-Tualang due to different processing method and equipments employed. To conclude, honey appeared to be compatible with PCM and produced stable suspension without the need for other excipients. The fusion of honey is also expected to confer its wholesome benefits to the pharmaceuticals and may improve the treatment of relevant indication.